Pharmacosomes: A Versatile Delivery System for Problematic Molecules - Rana, Pulkit; Mahajan, Ayush; Singh, Dilpreet; Singh, Kuldeep (Current Nanomedicine, 2021)
Amongst various lipids-based vesicular system, pharmacosomes bear unique advantage over various other lipid based vesicular system. Pharmacosomes are novel vesicular drug delivery system. Pharmacosomes impart better biopharmaceutical properties for synthetic and herbal drugs. Drug incorporated in pharmacosomes encompasses increased bioavailability, reduced toxicity and enhanced stability. Pharmacosome are generally prepared via phospholipid, but various drugs have been derived from different lipid moieties. These include fatty acyl derivatives, fatty alcohol derivative, cholesteryl derivatives. Pharmacosome were evaluated for different parameters such as size, surface morphology, drug entrapment, solubility and in vitro drug release rate. There has been advancement in the scope of this delivery system for several drugs used including NSAIDs, Anti-cancer, anti-viral, anti-hypertension and diuretic drugs. This article reviews the latent pharmacosome as a novel controlled and targeted drug delivery system and highlights the methods of preparation and characterization and application of pharmacosome in drug delivery for herbal and synthetic drugs.
Keywords: bioavailability